Self‐Rhythmic Soft Pneumatic Pressure Regulation System Based on Self‐Excited Oscillation of Jet Hose - Fenglin Han; Huang Xiong; Qixin Li; Jing Yang; Chunli He; Xueyi Guo; Zhi Chen (Advanced Intelligent Systems)
Most of pneumatic soft robots rely on external rigid controllers and valves to achieve rhythmic movements. This article introduces a soft pneumatic pressure regulation system with self‐rhythmic characteristics and simple structure. In this system, the hose generates self‐excited oscillations due to jet force, which realizes the transformation of constant pressure to periodically varying pressure. This mechanism allows soft robots to perform rhythmic movements. A mathematical model is developed to describe the self‐excited oscillations of the jet hose. Numerical simulations are conducted to analyze the impact of various parameters on system oscillations. The system operates under pressures from 90 to 150 kPa. By adjusting the pressure, hose length, and jet hole diameter, the oscillation frequency of the pressure can be tuned between 5.9 and 11.1 Hz. The comparison between simulation results and experimental data verifies the correctness of the mathematical model. Finally, a soft robot capable of crawling based on anisotropic friction is designed and fabricated. Powered solely by the soft pneumatic pressure regulation system, the robot achieves self‐rhythmic crawling. By adjusting the air source pressure, hose length, and jet hole diameter, the robot's crawling speed can be effectively controlled, ranging from 2.5 to 6.8 mm s−1.